Legal Analysis of Protection of Victims of Personal Data Abuse in Online Loans Based on Law Number 27 of 2022 and Its Implications for Digital Legal Justice in Indonesia - Dina Alfi Kurniawati; Ananda Megha Wiedhar Saputri; Burham Pranawa (Penerbit Hellow Pustaka, 2025)
The development of financial technology through online lending services (commonly known as pinjol) has significantly improved access to credit. However, it has also raised serious concerns regarding the protection of personal data. This research aims to analyze the legal protection against the misuse of personal data of online loan recipients based on Law Number 27 of 2022 on Personal Data Protection (PDP Law), and to examine its implications for the principles of digital legal justice in Indonesia. This study uses a normative juridical approach with descriptive-analytical methods supported by literature review on national regulations, relevant cases, and digital legal theory. The findings indicate that while the PDP Law provides a comprehensive legal foundation for the rights of data subjects and sanctions for violations, its implementation in the online lending sector faces structural and cultural obstacles. The high number of personal data misuse cases by illegal loan providers, weak regulatory oversight, and low digital literacy among users hinder the realization of substantial protection for victims. This condition reflects a gap between legal norms and actual protection in the digital space. Therefore, institutional strengthening, regulatory improvement, and increased digital legal literacy are essential to achieving digital justice that is both humane and effective in protecting the rights of all citizens.